2016
DOI: 10.1038/srep21018
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of alpha-mangostin against oxidative stress induced-retinal cell death

Abstract: It is known that oxidative stress plays a pivotal role in age-related macular degeneration (AMD) pathogenesis. Alpha-mangostin is the main xanthone purified from mangosteen known as anti-oxidative properties. The aim of the study was to test the protective effect of alpha-mangostin against oxidative stress both in retina of light-damaged mice model and in hydrogen peroxide (H2O2)-stressed RPE cells. We observed that alpha-mangostin significantly inhibited light-induced degeneration of photoreceptors and 200 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 37 publications
(38 reference statements)
11
64
0
2
Order By: Relevance
“…In a previous study, Marquez-Valadez et al found α-MG (10 μM, 25 μM and 50 μM) significantly increased GPx activity in rat brain synaptosomes with 3-NP-induced mitochondrial dysfunction [19]. Fang et al studied ARPE-19 cells with H 2 O 2 -induced high cellular stress and found α-MG treatment (200 μM) decreased TBARS levels and increased SOD, GPx and GSH activities [20]. Shen et al reported effects of α-mangosteen in the regulation of antioxidant sensor NRF2 transcription factor on regulation of transcription and redox status in adipocyte [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Marquez-Valadez et al found α-MG (10 μM, 25 μM and 50 μM) significantly increased GPx activity in rat brain synaptosomes with 3-NP-induced mitochondrial dysfunction [19]. Fang et al studied ARPE-19 cells with H 2 O 2 -induced high cellular stress and found α-MG treatment (200 μM) decreased TBARS levels and increased SOD, GPx and GSH activities [20]. Shen et al reported effects of α-mangosteen in the regulation of antioxidant sensor NRF2 transcription factor on regulation of transcription and redox status in adipocyte [21].…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al reported effects of α-mangosteen in the regulation of antioxidant sensor NRF2 transcription factor on regulation of transcription and redox status in adipocyte [21]. The authors attributed these observations to α-MG regulation of mitogen-activated protein kinases (MAPKs), extracellular signal-regulated kinase (ERK)1/2, JNK and p38 protein expression [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Mice from the Ctrl groups were housed on a 12-h dim light/dark cycle (dim light, ~5 lux). Mice in the BLE groups, as described in our previous work, 58 were exposed to cool blue light-emitting diodes (transmission peak wavelength: 480 nm, Zhongding Technology Co., Ltd. Shenzhen, China), which were positioned inside the cages on a 12-h light/dark cycle every day for up to 3 months (Supplementary Figure S2). We applied the illuminance intensity of 500 lux as it is measured as the normal room light intensity 59 and has been reported capable of causing retinopathy.…”
Section: Methodsmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) is known as an antioxidant and cytoprotective enzyme [8,9]. It has been reported that HO-1 confers protection against high glucose-induced toxicity in pancreatic β cells [10], retinal endothelial cells [11], and neurons [12].…”
Section: Introductionmentioning
confidence: 99%